Distribution pattern of the brackish Apocorophium lacustre (Vanhoffen, 1911) (Amphipoda: Corophiidae) and the structure of the amphipod assemblages in the upper Oder River catchment. Issue 3 (12th January 2021) - Krodkiewska, Mariola; Rewicz, Tomasz; Cebulska, Klaudia; Koczorowska, Adrianna; Konopacka, Alicja
Abstract: Apocorophium lacustre (Vanhoffen, 1911), which is a native brackish amphipod species of the North Atlantic and Baltic coasts, was recorded in the upper Oder River for the first time in 2017. Before that, only alien amphipod species had been found in this area. The aims of the study were to describe the distribution pattern of A. lacustre in the upper Oder River catchment, to investigate the composition and structure of the amphipod assemblages against the background of the habitat conditions and to provide a genetic identification of the species using DNA barcodes. In total, 16 sites were studied. A. lacustre was recorded in 14 of them. It was not found at one site in the Oder River and at one location in the lower Klodnica River. A. lacustre outnumbered the other amphipods in the Oder, in the mouth section of the Klodnica and at one site in the Gliwice Canal. The alien species Gammarus tigrinus  (Sexton, 1939) was dominant in the amphipod communities at the southernmost site in the Oder River, in the Klodnica Canal, and at most sites along the Gliwice Canal. In the Klodnica River, another alien species, Dikerogammarus villosus (Sovinsky, 1894), was dominant in the amphipod fauna at two sites. Though the density of A. lacustre was high in the Oder River, it was much lower in both the canals and the Klodnica River. In our study, the depth and river velocity both contributed to the distribution of this species.